IDENTIFICATION OF STARCH FORMS IN EDIBLE PLANTS - Lubis, Susi Mulianti; Sarjani, Tri Mustika; Mahyuni, Siska Rita; Pratiwi, Riska Tia; Faradina, Inka; Wardani, Sarwinda Kusuma; Fatimah, Siti; Halimatun, Futria; Parliansyah, M Rizky; Sheila, Andriana (Biotik, 2022)
This study aims to identify the forms of starch in edible plants. This research involved several edible plants such as sago, yam and taro. This type of research uses descriptive quantitative methods by conducting experiments on each sample used. The data collection technique was carried out by describing the results of the starch form from each sample that had been obtained. The results obtained from this study showed that the Sago preparations viewed under a microscope had an oval starch shape and spread throughout the preparation so that it was classified as an eccentric starch type that could be seen at 10X magnification, while Jicama starch preparations had a round starch shape and chains in some parts. The plane of the preparation and entered in the concentric type, but the shape of starch in Jicama can be seen under a microscope at 100X magnification, the Taro preparation has a round and lumpy shape but the starch accumulates in several areas of the preparation and enters the concentric type seen at 40X magnification. So it can be concluded that the forms of starch in edible plants are very diverse, both in round to oval shapes, with smooth and rough starch structures, namely in the form of lumps.Keywords: Edible Plants, Starch Form